Adsorption performances of the reusable ionic liquid–iron coordination complex (ILICC) adsorbent to remove reactive dyes. Issue 43 (13th September 2016) - Cheng, Dehong; Lin, Jie; Lu, Sheng; Hao, Xu; Lu, Yanhua
Abstract: In this paper, the reusable ionic liquid–iron coordination complex (ILICC) adsorbents were synthesized and applied to adsorb reactive dye. Adsorption performances of ILICC as solid-phase adsorbents to remove reactive dye were investigated. The percent of dye removal was 7.0% when 4.0 ml of 0.005 g L −1 reactive red B-3BD was directly adsorbed in the neutral condition by 0.02 g of ILICC. The percent of dye removal for the regenerated ILICC was 91.5% when ILICC was reused 10 times. Investigation of adsorption mechanism indicated that the adsorption force was electrostatic interaction between ILICC and reactive red B-3BD dye, and the mode of adsorption was Langmuir adsorption.